A Prospective Randomized Controlled Trial Comparing N-butyl-2 Cyanoacrylate (Histoacryl), Octyl Cyanoacrylate (Dermabond), and Subcuticular Suture for Closure of Surgical Incisions. Issue 1 (January 2015) - Koonce, Stephanie L.; Eck, Dustin L.; Shaddix, Kyle K.; Perdikis, Galen
Abstract : Introduction: The use of tissue adhesives for the closure of surgical incisions is increasing. Few studies directly compare tissue adhesives to one another or focus on the difference in wound closure time between tissue adhesives. We compared the use of N -butyl-2 cyanoacrylate (Histoacryl), octyl cyanoacrylate (Dermabond), or subcuticular suture in incisions resulting from reduction mammoplasty, mastopexy, panniculectomy, and abdominoplasty. Methods: A 2-armed prospective randomized controlled trial was performed. Part 1 compared closure of surgical incisions with N -butyl-2 cyanoacrylate and octyl cyanoacrylate. Part 2 compared the closure of surgical incisions with N -butyl-2 cyanoacrylate and subcuticular suture. End points were closure time, scar width, and satisfaction ratings. Results: Both study arms revealed significantly faster closer times with N -butyl-2 cyanoacrylate [9/10 in part 1 ( P = 0.022) and 10/10 in part 2 ( P = 0.002)]. Scar width difference did not reach statistical significance, and there was no difference in surgeon, independent reviewer, or patient satisfaction among the materials. Conclusions: Our results demonstrate a decreased time required for wound closure using N -butyl-2 cyanoacrylate compared to both suture and octyl cyanoacrylate regardless of incision type with no significant difference in scar width or satisfaction ratings.